The case of the missing mummy - Lantz, Francess (Scholastic Inc. New York, 1998)
The twins try to find the missing mummy at the museum. Mary-Kate and Ashley couldn't wait to see the mummy exhibit at their local museum. But when they got there, the mummy was gone! Joint the Trenchcoat Twins as they solve one of their most puzzling mysteries ever!